2006
DOI: 10.1186/1743-7075-3-41
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and age trends of metabolic syndrome and its risk factors: The Family Heart Study

Abstract: Background: We report longitudinal changes in the metabolic syndrome (MetS) in 2,458 participants from 480 families in the Family Heart Study. Participants were examined between 1994-96 (FHS-T1) and 2002-03 (FHS-T2), about 7.4 years apart. Additionally, the impact of medication on estimates of MetS prevalence, and associations of MetS with prevalent coronary heart disease (CHD) and type 2 diabetes (T2D) were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 27 publications
3
38
0
1
Order By: Relevance
“…We have previously found that PTSD is widely clinically underdiagnosed in this population [16], so that antipsychotic prescription rates may reflect primary psychotic disorders, but are unlikely used frequently for PTSD symptoms. Further, the magnitude of the effect of PTSD diagnosis on predicting the presence of metabolic syndrome was greater than the effect of age, which has been documented to increase the prevalence of each metabolic risk parameter, as well as prevalence of the overall metabolic syndrome [58]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously found that PTSD is widely clinically underdiagnosed in this population [16], so that antipsychotic prescription rates may reflect primary psychotic disorders, but are unlikely used frequently for PTSD symptoms. Further, the magnitude of the effect of PTSD diagnosis on predicting the presence of metabolic syndrome was greater than the effect of age, which has been documented to increase the prevalence of each metabolic risk parameter, as well as prevalence of the overall metabolic syndrome [58]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the detrimental health impact of metabolic syndrome is significant, with an approximate 2.5 fold increase in the odds of developing cardiovascular disease[58]. The magnitude of this risk highlights the public health impact of PTSD, and demonstrates the need for heightened vigilance for and treatment of metabolic syndrome within this population.…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is not surprising that the metabolic syndrome's prevalence is higher at older age. In a study that followed 480 families over about 7.4 years (between 1994-1996 and 2002-2003), the prevalence of the metabolic syndrome was about two to three times higher in those age 50 years and older compared with their younger counterparts [12]. In an analysis of data from NHANES 1999-2000, Ford et al [13] reported a graded association between older age and a higher prevalence of metabolic syndrome.…”
Section: Prevalence Of the Metabolic Syndromementioning
confidence: 97%
“…Although previous research suggests an increased prevalence of hyperlipidemia and hypertension in individuals with gout 33 , the high numbers of services for both groups of employees appear to be an unfortunate reflection of the increased rates of these specific diseases in the overall aging population 35 . The specific diagnostic categories did not allow for a determination of a measure of obesity or insulin resistance, two major components of the metabolic syndrome 23 .…”
Section: Discussionmentioning
confidence: 98%